Evaluasi Fitur Tracking pada Pengalaman Pelanggan di Bisnis Reparasi Smartphone - Adittia Fathah (Universitas Medan Area, 2022)
The aim of this research is to evaluate the tracking feature on customer experience using cell phone repair services. This research uses explanatory research method. The research sample taking method is the quota sampling method, namely 196 students at Sekolah Tinggi Teknologi Cipasung. Data collection was carried out by distributing questionnaires through the Google Form. The rating scale used is Likert. The data that has been collected is tested for its validity and reliability. The application used for data testing and visualization is Microsoft Excel. The results of data processing show that the resulting percentage value is between 80-100%. These results show consumers